Implementasi Kepemimpinan Transformasional Sekolah Meningkatkan Kinerja Guru Era Digital SDN 2 Watopute - Abubakar; Ezin Adistya (Digital Pedagogy in Primary Education Journal, 2026)
This study aims to analyze the implementation of transformational leadership by school principals in improving elementary school teachers’ performance in the digital era through a case study at SDN 2 Watopute. This study was motivated by the demands of educational digitalization, which require teachers to possess adequate pedagogical and technological competencies, while various challenges are still encountered in practice. This study employed a descriptive qualitative approach. The research subjects consisted of the principal, teachers, and educational staff selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through source and method triangulation. The findings indicate that transformational leadership was implemented through idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The principal promoted teachers’ digital competencies through training, academic supervision, and the development of a collaborative and innovative work culture. Supporting factors included the principal’s commitment, technological facilities, and organizational support, while inhibiting factors included limited digital literacy and resistance to change. Transformational leadership had a positive impact on teacher performance, particularly in the use of learning technology and innovation in teaching methods. Keywords: transformational leadership, school principal, teacher performance, digital era, elementary school